AUTOSOMAL DOMINANT, NON-AUTOIMMUNE, CONGENITAL HYPERTHYROIDISM - Mun, Vivian Lai How; Hua, Janet Hong Yeoh; Selveindran, Nalini M. (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Primary non-autoimmune hyperthyroidism is a rare cause of neonatal hyperthyroidism. This results from an activating mutation in the thyrotropin-receptor (TSHR). TSHR is a G-protein coupled receptor and is found primarily in the thyroid gland. It is also present in adipocytes, fibroblasts and bone cells. It can be inherited in an autosomal dominant manner or occur sporadically as a de novo mutation. Affected individuals display a wide phenotype from severe neonatal to mild subclinical hyperthyroidism. The severity of the hyperthyroid symptoms is variable and phenotype differences have been described in subjects harbouring the same mutation. CASE A 10-month-old female was born late preterm at 36 weeks via spontaneous vertex delivery with birth weight of 2.5 kg. Antenatally, the mother was asymptomatic for hyperthyroidism. There was no family history of thyroid or autoimmune diseases. The baby was referred at birth with deranged cord TSH of 0.05 miu/L. Repeat thyroid function tests at day 7 of life demonstrated an elevated T4 of 27.6 pmol/L and low TSH of 0.01 miu/L. She had persistently high free T4, hence, was started on carbimazole at 3 months old. She was also asymptomatic for hyperthyroidism. Her growth parameters were appropriate for age. She does not have dysmorphism. She had normal heart rate, blood pressure, and tone. She did not have a goiter. Her thyrotropin receptor autoantibodies were negative. Her neck ultrasound revealed a normal thyroid gland with normal vascularity, with no focal thyroid lesion seen. Genetic test revealed a heterozygous pathogenic variant in TSHR NM_000369.5:c.1891T>G (NP_000360.2:p. Phe631Val). During the course of follow-up, she was well and remained asymptomatic. CONCLUSION Although rare, TSHR gene mutation should be considered in an infant who presents with hyperthyroidism with a negative autoimmune screen and a negative maternal history of thyroid disorders. Early diagnosis is important so as to rapidly initiate anti-thyroid therapy and manage the thyrotoxicosis, to potentially avoid an enlarging goiter, and to prevent neurocognitive delays in young children with nonautoimmune hyperthyroidism.